Russia's Cultural Statecraft - Forsberg, Tuomas; Mäkinen, Sirke (Studies in Contemporary Russia, 2022)
This book focusses on Russia's cultural statecraft in dealing with a number of institutional cultural domains such as education, museums and monuments, high arts and sport. It analyses to what extent Russia's cultural activities abroad have been used for foreign policy purposes, and perceived as having a political dimension. Building on the concept of cultural statecraft, the authors present a broad and nuanced view of how Russia sees the role of culture in its external relations, how this shapes the image of Russia, and the ways in which this cultural statecraft is received by foreign audiences. The expert team of contributors consider: what choices are made in fostering this agenda; how Russian state authorities see the purpose and limits of various cultural instruments; to what extent can the authorities shape these instruments; what domains have received more attention and become more politicised and what fields have remained more autonomous. The methodological research design of the book as a whole is a comparative case study comparing the nature of Russian cultural statecraft across time, target countries and diverse cultural domains. It will be of interest to scholars and students of Russian foreign policy and external relations and those working on the role of culture in world politics.